Additional file 6 of Genomic evidence for sulfur intermediates as new biogeochemical hubs in a model aquatic microbial ecosystem - Adrien Vigneron (10162165); Perrine Cruaud (10162168); Alexander I. Culley (10162171); Raoul-Marie Couture (10162174); Connie Lovejoy (10162177); Warwick F. Vincent (10162180) (2021)
Additional file 5: Supplementary Table S1. Description of the genomic bins with sulfur-cycling genes identified in the Lake A microbiome presented in Figure 3.